Mid-range management theory : competence perspectives on modularity and dynamic capabilities - Sanchez, Ron; Heene, Aimé; Polat, Seçkin; Asan, Umut (Emerald Publishing Limited, 2017)
This volume presents an epistemological argument for the essential function of mid-range theory in advancing management concepts that can be usefully applied by managers. Authors analyse two examples - modularity and dynamic capabilities.- Resumé vydavatel
Obsahuje index.
Keywords: management; strategický management; rozhodování; strategic planning; decision making; sborníky; elektronické knihy; papers of several authors; electronic books